Comparison of the rate of complications in primary and secondary enucleation in patients with retinoblastoma - Rabeeah Zafar; Altaf, Sumaira; Noorani, Sorath; Jabeen, Sidra; Hassan, Shadab (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the complications after primary and secondary enucleation in children with retinoblastoma. Method: The prospective cohort study was conducted from January 1, 2017, to December 31, 2022, at the Children Eye Hospital, Al-Shifa Trust, Rawalpindi, Pakistan, and comprised children with retinoblastoma who underwent enucleation. Post-enucleated sockets in the patients were evaluated for any post-operative complications. Data was analysed using SPSS 26. Results: Of the 133 patients with mean age 28.1±19.1 months, 77(58%) were boys and 56(42%) were girls. Overall, 74(56%) patients had primary enucleation, 59(44%) had secondary enucleation, 79(59%) had unilateral disease and 54(41%) had bilateral retinoblastoma. Family history was positive in 23(17%) patients. The difference between age at presentation between primary and secondary enucleation was not significant (p=0.619). Complications were observed in 28(21.1%) sockets, the most common being implant exposure 9(32%). The rate of complications between primary and secondary enucleation cases was not significant (p=0.80). Female gender (p=0.02, odds ratio: 1.6, 95% confidence interval: 1.109-2.410), intravenous chemotherapy (p=0.11, odds ratio: 1.2 95%, confidence interval: 0.980-1.594), high-risk features (p=0.02, odds ratio: 1.7 95%, confidence interval: 1.127-2.608) and extraocular disease (p=0.49, odds ratio: 1.1, 95% confidence interval: 0.759-1.796) were associated with greater odds of developing complications post-enucleation. Conclusion: Complications were observed in more than one-fourth of the enucleated sockets. Intravenous chemotherapy, female gender, high-risk features and extraocular retinoblastoma added to the burden of post-operative complications. Key Words: Retinoblastoma, Postoperative complications, Enucleation, Chemotherapy, Histopathology.